2007
DOI: 10.1111/j.1524-4725.2007.34008.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Study Comparing the Action Halos of Two Commercial Preparations of Botulinum Toxin Type A

Abstract: Injections of Dysport and BOTOX at an equivalence ratio of 2.5:1 U, respectively, applied at the same volume and depth, using the same technique resulted in similar action halos with regard to muscular and sweat gland activity. Both products seem to be safe and very predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
2
26
0
1
Order By: Relevance
“…15,16 The scale has the advantage of measuring the field of BoNT-A effect without the need for the Minor’s test, which has often been used to demonstrate localized and/or comparative effects of BoNT-A in areas such as the frontalis. 31-33 The FMS assessment relies on a series of photographs using the same camera settings and lighting conditions with a rest period of 1 minute between photographs (Table 1). Using the frontalis muscle also allows for bilateral (split-face) comparison of different toxins, dosing and technique on a single patient.…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 The scale has the advantage of measuring the field of BoNT-A effect without the need for the Minor’s test, which has often been used to demonstrate localized and/or comparative effects of BoNT-A in areas such as the frontalis. 31-33 The FMS assessment relies on a series of photographs using the same camera settings and lighting conditions with a rest period of 1 minute between photographs (Table 1). Using the frontalis muscle also allows for bilateral (split-face) comparison of different toxins, dosing and technique on a single patient.…”
Section: Definitionsmentioning
confidence: 99%
“…Hexsel et al have demonstrated the relationship between muscle weakening halos and sweating halos in their forehead model. 31-33 Because the face contains so many muscles, an injection site may overlap a non-target muscle, particularly if the toxin diffuses more widely than expected. 35 Conversely, if the toxin used does not develop the same field of effect obtained with another toxin, patients may not achieve the expected results.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite widespread clinical use, comparative dose ratios or conversion factors of BTX-A formulations remain controversial because they have been shown to have differences in efficacy and systemic effects (Kim et al 2013). Hexsel et al (2008) reported similar field effects at a dose equivalence of 2.5:1.0 IU (Dysport®:Botox®) for both muscle and sweat gland activity. Bearing in mind that both authors, Steel et al (1997) and Christiansen et al (2004), applied 5 IU of onabotulinumtoxinA (ona-BoNT/ A; Botox®, Allergan, Inc, Irvine, CA) and based on the reported conversion ratio observed by Hexsel et al (2008) between onabotulinumtoxinA (ona-BoNT/A; Botox®, Allergan, Inc, Irvine, CA), abobotulinumtoxinA (abo-BoNT/A; Dysport ® Ipsen LTD, Wrexham, UK), we decided to apply a single dose of 12.5 IU of Dysport ® BTX-A (corresponding to 5UI Botox®) into the medial region of the orbicularis muscle in the lower eyelid in patients with epiblepharon to ease symptoms and prevent ocular surface complications related to this disease.…”
Section: Introductionmentioning
confidence: 99%
“…orbicularis oculi) 1–2 sites of injection and a quantity of 3–4 units are effective, whereas a large muscle (e.g. gastrocnemius) requires 4–5 injections and 300–400 units [72, 73]. Typically, a spastic muscle initially receives a small quantity (e.g., 10 units) of the toxin in order to evaluate several reactions (e.g., paralysis, allergy).…”
Section: Pharmaceutical Preparations Of Botulinum Neurotoxinsmentioning
confidence: 99%